Polymorphism of rs3813034 in Serotonin Transporter Gene SLC6A4 Is Associated With the Selective Serotonin and Serotonin-Norepinephrine Reuptake Inhibitor Response in Depressive Disorder: Sequencing Analysis of SLC6A4. Issue 1 (February 2016) - Nonen, Shinpei; Kato, Masaki; Takekita, Yoshiteru; Wakeno, Masataka; Sakai, Shiho; Serretti, Alessandro; Kinoshita, Toshihiko
Abstract : Abstract: Selective serotonin and serotonin-norepinephrine reuptake inhibitors (SSRI/SNRI) are commonly used for treating major depression. Regretfully, significant heterogeneity exists regarding the benefits of SSRI/SNRI in individual cases. We previously reported that a polymorphism located in the serotonin transporter linked promoter region (5-HTT LPR) is associated with an interindividual difference in SSRI treatment efficacy. However, this explains only a small part of the variation of this complex phenotype. Other 5-HTT variants in the coding regions, 3′ untranslated region (3′ UTR), and introns adjacent to each exon could also contribute to treatment response. Therefore, we performed a sequencing analysis of the SLC6A4 gene (coding for 5-HTT) and investigated the association between variants detected in this study and the antidepressant response to SSRI/SNRI in 201 Japanese depressive patients. Seventeen novel mutations were identified by sequencing analysis. We found that the polymorphism G2563T (rs3813034) as a tag single-nucleotide polymorphism of IVS9 A-90G (rs140701), G2356T (rs1042173), and A3641C (rs7224199) is associated with interindividual variability of SSRI/SNRI efficacy at week 6, independent from clinical variables and effect of 5-HTT LPR ( P < 0.001 by multiple regression analysis). This polymorphism could help determine individualized SSRI/SNRI treatments for depressive patients in combination with 5-HTT LPR.